2014
DOI: 10.5194/soild-1-267-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Litter decomposition rate and soil organic matter quality in a patchwork heathland of Southern Norway

Abstract: Abstract. Norwegian heathland soils, although scant and shallow, are major reservoirs of carbon (C). We aimed at assessing whether vegetation cover and, indirectly, its driving factor soil drainage are good proxies for soil organic matter (SOM) composition and dynamics in a typical heathland area of Southern Norway consisting in a patchwork of three different types of vegetation, dominated by Calluna, Molinia, or Sphagnum. Such vegetation covers were clearly associated to microtopographic differences, which in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…For heath soils, wide C/N ratio of >30 (Rowe et al ., ) or >20 (Certini et al ., ) has been observed. Wide C/N ratio is also common in peat soils (Aitkenhead & McDowell, ), but in cultivated peatlands, C/N ratio can decrease as a consequence of drainage and agricultural management (Krüger et al ., ).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…For heath soils, wide C/N ratio of >30 (Rowe et al ., ) or >20 (Certini et al ., ) has been observed. Wide C/N ratio is also common in peat soils (Aitkenhead & McDowell, ), but in cultivated peatlands, C/N ratio can decrease as a consequence of drainage and agricultural management (Krüger et al ., ).…”
Section: Discussionmentioning
confidence: 83%
“…Lower specific SOC mineralisation rates have been found in sandy historical heath soils with partly high groundwater levels in north‐west Germany than in reference Cambisols (Springob & Kirchmann, ). It has been shown that heath litter and SOC under heath vegetation contain high concentrations of alkyl C, mainly comprising lipids, waxes, resins and suberin, and have relatively high hydrophobicity index (Certini et al ., ), impeding microbial decomposition of the organic material (Bachmann et al ., ). Cropland soils on historical heath still contain large proportions of lipids, although they may be not as high as in permanent heath (Sleutel et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…This study investigates rainfall‐triggered sediment reallocations to enable sustainable land management at catchment scale. However, the sedimentological response of a landscape is complex, because it depends on a variety of interacting physical processes, which are related to topography, climate, soil and vegetation among others (Martínez‐Mena et al, ; Cammeraat, ; Puigdefábregas, ; Bracken & Croke, ; Bautista et al, ; Bochet, ; Certini et al, ; Marchamalo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the human activities can be sustainable and some strategies as mulching, cash crops, low intensity grazing, or organic farming can help to achieve the sustainability (Costantini et al ., ; Li et al ., ; Lu et al ., ; Prosdocimi et al ., ). Hedgerows contribute to improve the land management as they imitate nature strategies such as the patchy or strip plant covers (Bochet, ; Cerdà, ; Certini et al ., ). They have been recognised as valuable habitats for a variety of wildlife as they provide refuge and food resources for many species, some of them threatened, or rare species of high conservation status (Dover & Sparks, ; Wilson, ).…”
Section: Introductionmentioning
confidence: 99%